1989
DOI: 10.1007/bf01092407
|View full text |Cite
|
Sign up to set email alerts
|

The use ofEscherichia coli mutants to measure the bioavailability of essential amino acids in foods

Abstract: The beta-galactosidase-based assay for lysine developed by Tuffnell & Payne was used to measure the bioavailabilities of cyst(e)ine, methionine, threonine and tryptophan in pronase digests of 17 foods. The digests were assayed by estimating the beta-galactosidase synthesis responses of five Escherichia coli mutants, each requiring one of the respective amino acids for protein synthesis. Deletion mutants were used whenever possible in order to ensure strain stability. Single digests of each food were assayed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…Casein and whole dried egg are both highly available protein sources, with casein considered to be completely available. 16,30 Poultry by-product meal, however, has lower and more highly variable amino acid digestibility than casein or egg. 27,32 When comparing enzyme treatment only on the protein sources, protease as a single-enzyme digest was as complete at digesting the protein sources as a multiple-enzyme treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Casein and whole dried egg are both highly available protein sources, with casein considered to be completely available. 16,30 Poultry by-product meal, however, has lower and more highly variable amino acid digestibility than casein or egg. 27,32 When comparing enzyme treatment only on the protein sources, protease as a single-enzyme digest was as complete at digesting the protein sources as a multiple-enzyme treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Pepsin, chymotrypsin, trypsin, peptidase and protease all have been utilised. 11,13,16 Based upon a mixture of protease and peptidase producing the most extensive digest, this enzyme combination has been recommended for use. 11 However, the duration of enzyme treatment of the protein sources for E coli has varied in studies from 2 to 16 h. 11,16 The duration of the enzyme hydrolysis can affect the total quantity of amino acids and peptides released.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitchens et al [45] demonstrated that E. coli GUC41 could grow on DL-methionine sulfoxide but not on DL-methionine sulfone. The microbiological assay was as accurate as the chemical assay with high correlation coefficients between the two.…”
Section: E Coli As a Biosensor For Amino Acid Bioavailabilitymentioning
confidence: 99%
“…Several attempts have been made to develop rapid methods to estimate lysine bioavailability in foods and feeds, including chemical methods [2,3] and microbiological assays [4,5]. Even though the analytical chemical methods are more rapid when compared to the conventional animal bioassays, they fail to measure lysine availability accurately [6,7].…”
Section: Introductionmentioning
confidence: 99%